Evaluation of the Stability of the Anaerobic Digestion Process of POME Based on the Correlation of VFA, Alkalinity and Methane Content - Anang Baharuddin Sahaq; Agung Kurnia Yahya; Resi Levi Permadani; Salwa Asyifa; Aulia Firda Alfiana (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2026)
Palm Oil Mill Effluent (POME) contains a high organic load and requires effective treatment to prevent environmental pollution while enabling energy recovery. Anaerobic digestion is widely applied for POME treatment due to its ability to reduce organic pollutants and produce methane-rich biogas; however, its performance is highly dependent on process stability. This study aims to evaluate the stability of the anaerobic digestion process of POME through correlation analysis among volatile fatty acids (VFA), total alkalinity (TA), suspended solids (SS), and methane content (CH₄) using field operational data. The study was conducted at an industrial-scale biogas plant treating POME, where slurry samples were collected periodically from multiple biodigester units representing different digestion stages. VFA and TA were analyzed using acid–base titration, SS by gravimetric method, and methane content using a gas analyzer. The results show that the anaerobic digestion process operated under stable mesophilic conditions (35 ± 2 °C) with reactor pH maintained in the optimal range of 6.8–7.5. VFA concentrations remained relatively low (approximately 480–510 mg/L), supported by sufficient alkalinity (about 5,600 mg/L as CaCO₃), resulting in a low VFA/TA ratio ( 0.09), indicating stable process conditions. A significant reduction in COD from approximately 41,700 ppm in the influent to about 7,200 ppm in the effluent was achieved, corresponding to a COD removal efficiency of 83%. Methane content in the biogas remained stable at ≥55%, supporting effective energy utilization without flaring. These results demonstrate that maintaining a balanced relationship among VFA, alkalinity, suspended solids, and operating conditions is essential for ensuring stable anaerobic digestion and consistent biogas quality in industrial-scale POME treatment systems.